Differences in Personal Social Development Before and After Role Playing in Preschool Children 4-5 Years Old - Masfi, Achmad; Ramadhan, Muhammad Putra; Rahmatika, Qory Tifani; Evi, Nurul; Afiani, Nurma; Sunaryo, Eri Yanuar Akhmad Budi; Widjayanti, Yhenti (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2023)
4-5 year olds should learn to improve personal social development. One effective way to improve personal social development is to play a role. The purpose of this study was to determine the differences in role play in personal social development in preschoolers (ages 4-5 years). The methode this research is Pre-experimental design using One Group Pra Post test design with sample of 30 respondents. The Sampling technique using purposive sampling using statistical test of Wilcoxon. A data Collection is done use Denver II only on the social development sector before intervention and after intervention. The result of the research shows that before the intervention of playing role as much as 25 (80,6%) children experience delay in personal social development. After playing role intervention role play a number of 12 children experience improvement in personal social development, so a number of 10 (32,2%) normal child 18 (58,1%) coution 3 (9,7%) child delayed. The result of statistical test shows that there is a difference of role play to social development in preschool children (4-5 years) with significant value 0,001 (0,001 <0,05). The conclusion in this study is that proper simulation of preschoolers should be done to improve the social development of children.